Therapeutic of Mesenchymal Stem Cells in Diabetes - Susanti Vinski, Deby; Cinta Vinski Borneo, Natasha (Riviera Publishing, 2023)
This study aims to explain and analyze the effective treatment of diabetes mellitus by Mesenchymal Stem Cells with respect to traditional therapy based on oral anti-diabetic drugs. As well as to study its regularly consistent properties. The method used in this research is the case study method. Patient care records were the main source of data for this study including evaluation and analysis. So that the results of the study explain that at the same time the utilized products cultured by